Association Between Vitamin D Levels and Treatment Response to Direct-Acting Antivirals in Chronic Hepatitis C: A Real-World Study - Gayam, Vijay (Gastroenterology Res, 2018)
BACKGROUND: Low serum vitamin D levels in chronic hepatitis C (CHC) is associated with advanced liver fibrosis; and there remains an imprecise relationship with the treatment response based on the vitamin D levels. Previous studies have shown conflicting results on the vitamin D levels, and association with treatment response in CHC treated with interferon-based regimens. METHODS: Patients with CHC treated with direct-acting antivirals (DAAs) between January 2016 and December 2017 in the community clinic setting were retrospectively analyzed. Pretreatment baseline patient characteristics, treatment efficacy with the sustained virologic response at 12 weeks post-treatment (SVR 12) were assessed in CHC patients with deficient, insufficient, and normal levels of vitamin D measured before the initiation of DAA therapy. RESULTS: Two hundred and ninety-one patients were included in the study. Direct-acting antivirals included in the study were ledipasvir/sofosbuvir ± ribavirin, ombitasvir + paritaprevir + ritonavir + dasabuvir ± ribavirin, and sofosbuvir/velpatasvir. An overall sustained virologic response was achieved in 95% (n = 276) of patients. SVR 12 rates among patients with vitamin D deficiency, vitamin D insufficiency and normal vitamin D levels were 92%, 96.2%, and 97.2% respectively and was not statically significant (P = 0.214). A total of 71 patients were cirrhotic. The prevalence of vitamin D insufficiency (20 - 29.9 ng/mL) and deficiency (< 20 ng/mL) was significantly higher in cirrhotic patients (P = 0.01). Despite this, pretreatment vitamin D levels did not show any impact on the virologic response. The most common adverse effect observed was fatigue. None of the patients had to discontinue the treatment due to adverse events. CONCLUSIONS: DAAs are safe and effective with a high overall SVR 12 in CHC and treatment response does not depend on the pretreatment vitamin D levels. The prevalence of both vitamin D insufficiency and deficiency was observed to be higher in cirrhotic cohorts compared to non-cirrhotic counterparts.